Breaking the Gridlock: Can Teman Bus Transform Ubud’s Traffic Woes? - Putu Puja, Ida Bagus; Winatha , Mahendra Adi; Retnasamy, Vithyacharan; Aryasih, Putu Ayu (Politeknik Pariwisata Makassar, Indonesia, 2025)
Traffic congestion in Ubud, Bali, is a significant issue affecting both the quality of tourist experiences and the daily lives of residents. The Teman Bus program, a public transportation initiative, is expected to alleviate congestion by providing a more efficient mass transit alternative. However, the program's implementation faces challenges, particularly regarding the bus sizes that are unsuitable for Ubud's narrow roads, as well as criticism from local residents who feel its contribution to reducing congestion has been minimal. This study aims to evaluate the impact of the Teman Bus program on traffic congestion in Ubud from the perspectives of local residents and tourists. Data were collected through surveys and interviews with Ubud residents and tourists who use the Teman Bus service. The findings indicate that while Teman Bus has the potential to reduce congestion, its effectiveness is limited by the mismatch between bus sizes and road conditions, as well as the lack of awareness and information about the service. Recommendations include the use of smaller buses, improvements to routes and schedules, and enhanced outreach to both local communities and tourists. The study concludes that achieving the goal of reducing congestion requires adjustments to the implementation of the Teman Bus program to better align with the needs of Ubud's local and tourism sectors.